Analysis of Three Phase Induction Motor Supplied by SVPWM Inverter for Electric Bike Application - Hamzah, Amir; Hutabalian, Ronaldi; Suwitno, Suwitno; Romy, Romy (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Electric drive on an electric bike, consist of electric motor, power converter and electronic controller. These are the mover of electric vehicle system. This paper discussed the three-phase inverter with Space Vector Pulse Width Modulation (SVPWM) method as a three-phase induction motor drive in electric bike application. The discussed that are modeled by using MATLAB/SIMULINK. The purpose of this paper is to get the analysis of the three-phase inverter SVPWM as a three-phase induction motor drive with specification 500 W, 50 V, 50 Hz and 8 poles. Converter using a battery with a voltage 48 V. Before the battery voltage is converted by an inverter, battery voltage was increased through a boost converter up to 70.62 V. Through simulation with MATLAB software was obtained curve of sinusoidal voltage, current, and speed of the motor by SVPWM controlled system. In this paper also tested against changes in the value of the fundamental frequency inverter. Test results show that the inverter can be set the speed of the motor at a frequency of 20 Hz to 50 Hz. Electric drive on an electric bikes, consist of electric motor, power converter and electronic controller. These are the mover of electric vehicle systems. This paper discussed the three-phase induction motor supplied by Space Vector Pulse Width Modulation (SVPWM) inverter. They discussed that are modeled by using MATLAB/SIMULINK. The purpose of this paper is to get the analysis of the three-phase inverter SVPWM as a three-phase induction motor drive with specification 500 W, 50 V, 50 Hz and 8 poles. Converter using a battery with a voltage 48 V .